Validating reported cause of death using integrated electronic health records from a nation-wide database. (28th November 2019) - Leventer-Roberts, Maya; Haklai, Ziona; Applbaum, Yael; Goldberger, Nehama; Cohen, Dror; Levinkron, Ohad; Feldman, Becca; Balicer, Ran
Abstract: Background: To compare the underlying cause of death reported by the Israeli Central Bureau of Statistics (CBS) with diagnoses in the electronic health records (EHR) of a fully integrated payer/provider healthcare system. Methods: Underlying cause of death was obtained from the CBS for deaths occurring during 2009–2012 of all Clalit Health Service members in Israel. The final cohort consisted of members who had complete medical records. The frequency of a supportive diagnosis in the EHR was reported for 10 leading causes of death (malignancies, heart disease, cerebrovascular disease, diabetes, kidney disease, septicemia, accidents, chronic lower respiratory disease, dementia and pneumonia and influenza). Results: Of the 45 680 members included in the study, the majority of deaths had at least one diagnosis in the EHR that could support the cause of death. The lowest frequency of supportive diagnosis was for septicemia (52.2%) and the highest was for malignancies (94.3%). Sensitivity analysis did not suggest an alternative explanation for the missing documentation. Conclusions: The underlying cause of death coded by the CBS is often supported by diagnoses in Clalit's EHR. Exceptions are septicemia or accidents that cannot be anticipated from a patient's EHR, and dementia which may be under-reported.